(untitled) (Bangladesh Journal of Medical Science, 2020)
Background: Lower level of maternal serum hemoglobin (Hb) concentration may cause adverse pregnancy outcome (LBW, Preterm delivery) have been inconsistent. Many studies have been shown the impact of Hb concentration and protein status on pregnancy outcome in GA<37 weeks of pregnant mother. Objectives: The study was carried out to measure serum Hb concentration correlated with TP level on birth outcomes in GA <37 weeks of delivery mother. Method: This observational study was carried out in the Department of Physiology Sir Salimullah Medical College Mitford Hospital, Dhaka. A total number of 108 subjects were included in this study. They were divided into two groups among them 27 full term delivery mother gestational age (>37 wks) with their respective neonates (control group). The study group consisted of 27 Preterm delivery mothers gestational age (<37 wks) with their respective neonates (study group). Age ranged of both (control & study) pregnant mother were from 20- 40 yrs. The serum Hb and TP level of all participants were estimated by usual lab technique (Autoanalyser) in laboratory of department of Physiology, SSMC to observe the availability of binding protein. Independent samples t test, and Pearson’s correlation were done by as a test of significance. p value <0.05 was considered as significant. Statistical analysis was done by using SPSS Programme, Version-15. Result: Mean serum Hb level were significantly higher (p<0.01) and serum total protein level were significantly lower in gestational age <37 weeks pregnant mother (study) in comparison to gestational age >37 weeks of pregnant mother(control). Again, cord serum TP concentration of neonates were significantly (p<0.001) lower in gestational age <37 weeks of neonates compared with gestational age >37 weeks neonates of their respective mother. On the other hand, mean birth weight (≥2.5kg) and APGUR score both at 1st and 5th minute (≥8) were significantly (p<0.001) lower in neonates of gestational age<37weeks than that of, gestational age>37weeks neonates of their respective mothers. Conclusions: The present study revealed significantly reduced hemoglobin &lower cord blood protein concentration in neonates and &TP level of their respective mothers whose are gestational age <37 weeks. Abnormal hemoglobin concentrations causes increase the risk of adverse birth outcomes LBW, poor APGUR score; these may be due to poor maternal protein status. Bangladesh Journal of Medical Science Vol.19(2) 2020 p.278-283